Bacterial coinfection and antibiotic resistance in hospitalized COVID-19 patients: a systematic review and meta-analysis - Ruhana Che Yusof; Mohd Noor Norhayati; Yacob Mohd Azman (PeerJ, 2023)
Background There were a few studies on bacterial coinfection in hospitalized COVID-19 patients worldwide. This systematic review aimed to provide the pooled prevalence of bacterial coinfection from published studies from 2020 to 2022. Methods Three databases were used to search the studies, and 49 studies from 2,451 identified studies involving 212,605 COVID-19 patients were included in this review. Results The random-effects inverse-variance model determined that the pooled prevalence of bacterial coinfection in hospitalized COVID-19 patients was 26.84% (95% CI [23.85–29.83]). The pooled prevalence of isolated bacteria for Acinetobacter baumannii was 23.25% (95% CI [19.27–27.24]), Escherichia coli was 10.51% (95% CI [8.90–12.12]), Klebsiella pneumoniae was 15.24% (95% CI [7.84–22.64]), Pseudomonas aeruginosa was 11.09% (95% CI [8.92–13.27]) and Staphylococcus aureus (11.59% (95% CI [9.71–13.46])). Meanwhile, the pooled prevalence of antibiotic-resistant bacteria for extended-spectrum beta-lactamases producing Enterobacteriaceae was 15.24% (95% CI [7.84–22.64]) followed by carbapenem-resistant Acinetobacter baumannii (14.55% (95% CI [9.59–19.52%])), carbapenem-resistant Pseudomonas aeruginosa (6.95% (95% CI [2.61–11.29])), methicillin-resistant Staphylococcus aureus (5.05% (95% CI [3.49–6.60])), carbapenem-resistant Enterobacteriaceae (4.95% (95% CI [3.10–6.79])), and vancomycin-resistant Enterococcus (1.26% (95% CI [0.46–2.05])). Conclusion All the prevalences were considered as low. However, effective management and prevention of the infection should be considered since these coinfections have a bad impact on the morbidity and mortality of patients.